Enhanced hydrogen sorption properties of MgH2 when doped with mechanically alloyed amorphous Zr0·67Ni0.33 particles. (23rd October 2020) - Dong, Jinjian; Panda, Subrata; Zhu, Wen; Zou, Jianxin; Ding, Wenjiang
Abstract: In the present study, the effect of amorphous Zr0·67 Ni0.33 additive containing nano-ZrO2 on the hydrogen sorption kinetics and thermodynamics of Mg/MgH2 was investigated. The amorphous Zr0·67 Ni0.33 particles prepared by mechanical alloying of stoichiometric elements were introduced into MgH2 powder through high-energy milling to produce a MgH2 /Zr0·67 Ni0.33 composite. Structural and morphological analyses revealed that the nanostructuring effect of the ZrO2 containing amorphous Zr0·67 Ni0.33 has led to significant grain-size refinement of MgH2 to the nanometric scale. As a result, the MgH2 /Zr0·67 Ni0.33 composite demonstrates enhanced hydrogenation and dehydrogenation kinetics (4.0 wt%/50 s/250 °C and 5.0 wt%/4 min/325 °C, respectively). Meantime, substantially lowered enthalpies (−63.40 and 67.06 kJ/mol H2 obtained through pressure-composition-isotherm measurements) and reduced desorption temperature ( 270 °C) were observed in the composite as compared to the pure MgH2, possibly due to the dissolution of Ni into MgH2 lattice during ball milling. Highlights: Amorphous Zr0·67 Ni0.33 particles containing nano ZrO2 are prepared by mechanical milling. Amorphous Zr0·67 Ni0.33 acts as process control agent to reduce MgH2 particles size. Formation of nano ZrO2 in Zr0·67 Ni0.33 enhances hydriding/dehydriding kinetics of MgH2 . Solid solution of Ni in Mg/MgH2 improves hydrogen sorption thermodynamics of MgH2 .